PEMANFAATAN LOOSE PARTS PADA PENDIDIKAN ANAK USIA DINI - Srinah Yanti (JGK (Jurnal Guru Kita), 2022)
Abstract: Utilization of Loose Parts In Early Children Education.This paper aims to explain the concept of loose parts to provide a correct understanding when adapting it into the form of learning or playing activities for early childhood. The approach used is literature study through research results and theories related to lose parts and learning for early childhood. Abstrak: Pemanfaatan Loose Parts Pada Pendidikan Anak Usia Dini. Tulisan ini bertujuan  memaparkan konsep loose parts sehingga memberi pemahaman yang benar saat mengadaptasi ke dalam bentuk pembelajaran atau kegiatan main pada anak usia dini. Pendekatan yang digunakan adalah dengan studi kepustakaan melalui hasil riset dan teori terkait loose parts serta pembelajaran untuk anak usia dini